Trinidad and Tobago. Significant achievements 2010 - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2022)
The main activities carried out by the Institute in Trinidad and Tobago during 2010 are identified, with respect to the needs and interests of the country, strengthening issues such as agribusiness, export, organic agriculture, agrotourism, training, labeling, packaging, food safety, journalism. agriculture, marketing, food production, decision-making, marketing, inclusion of women and the value chains of coffee, cocoa and chili peppers.